AN OVERVIEW OF INTERNET COMMUNICATIONS AS ONE OF THE ASPECTS OF THE CONVERGENCE DEVELOPMENT OF REGIONS OF UKRAINE - Savchyn, I. Z.; Tsareva, O. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The modern stage of Internet communications industry development is characterized by a large-scale breakthrough in the field of economics informatization. Development and optimization of Internet communications improves the effectiveness of enterprises, and therefore has a direct impact on the economic development of its region. The obtained results of the analysis of researches of domestic and foreign scientists allowed outlining the problems of communication processes in terms of convergence. The ways of increasing the level of development of Internet communications as one of the factors of improving the level of communication processes in the region's economy are proposed.